THE DEMANDS OF USING ARTIFICIAL INTELLIGENCE-DRIVEN SOFTWARES IN EDUCATION TOWARDS THE INDUSTRIAL REVOLUTION 6.0: A REVIEW OF STUDIES - Tabuena, Almighty Cortezo; Tabuena, Yvon Mae Hilario (International Journal of Education, 2025)
Artificial Intelligence (AI) has gained significance attention among educational scholars since it helps transform and advance the way education is delivered, making it more efficient, personalized, and accessible for all students. However, the extent to which the use of AI technology is demanded in the education sector requires further review among the existing literature. This study examines the demands of Artificial Intelligence (AI) integrating software in the context of Industrial Revolution 6.0 and its impact on education. The Technology Acceptance Model serves as a basis for investigating how individuals adopt and use new technology. A descriptive method and a qualitative research approach were used to review and synthesize emerging concepts related to the demands of AI integrating software in education. The findings suggest that AI integration can enhance personalized learning experiences and optimize resource allocation for students and educators. However, privacy concerns, bias, and ethical considerations must also be taken into account. The demands of Industrial Revolution 6.0, such as technical skills and global competence, require a focus on critical thinking, creativity, and lifelong learning. To leverage technology and innovation while fostering a culture of innovation, a holistic approach that includes project-based learning and professional development is necessary. Adapting to the demands of AI and Industrial Revolution 6.0 has significant implications for teaching methods and ethical considerations and is crucial for preparing students for the future workforce.